Approximation of functions regular in convex polyhedrons by exponential polynomials of a special form - Melnik , Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We construct exponential polynomials of special form which sufficiently well approximate functions that are regular in an open convex polygon and continuous on its closure.